formation of Pith Flecks and Pattern of Compartmentalization in Response to Fungal Infection in Derris Trifoliata Lour., (fabaceae) - Koyani, Rina D.; Patil, Vidya S.; Rajput, Kishore S. (Indian Forester, 2014)
Pattern of compartmentalization in response to fungal invasion is studied in a mangrove associate Derris trifoliata Lour., (Fabaceae) by histological and histochemical methods. Cambium miners form boreholes in the stem by making tunnels through bark into the cambial region. Injury formed on the xylem side, induce formation of callus like cells that differentiate into pith flecks while, cells lining the tunnel on phloem side differentiate into cork cells. Boreholes formed by cambial miners provide platform to various pathogenic fungi to invade various cells of xylem. Fungal hyphae enter into vessel lumen and travel from vessels to rays and adjacent xylem elements through the pits present on the lateral walls. To compartmentalise the fungal invasion, paratracheal parenchyma accumulate phenolic compounds that completely ensnare infected portion of xylem from all the sides. Subsequently, adjacent parenchyma release phenolic compounds into the vessel lumen and completely embeds the hyphae within it. In case of severely infected samples, parenchyma cells between normal and infected xylem produce interxylary cork as a barrier zone. The wound callus induced in response to larval mining activity possessed parenchymatous cells and are derived from the ray and xylem mother cells.